Neighboring Rights dalam Sengketa Penyiaran (Free to Air) Studi Komparasi Hukum Indonesia dan Korea Selatan - Murniatun, Murniatun; Fuad, Fokky (UNES Law Review, 2024)
Broadcasting institutions as one of the creators included in the neighboring right group often face economic rights violations that cause losses of up to trillions of rupiah. It is undeniable that the value of copyrighted works of intellectual products of the human mind needs to be appreciated with an economic orientation to realise the welfare of the creators' lives. In Indonesia and South Korea, economic rights violations against copyrighted works of broadcasting occur. The case at the end of January 2024 related to organised intellectual property rights violations no longer falls into the realm of civil law but can also be charged with criminal law. The case is related to the arrest of a South Korean citizen who committed an organised copyright crime with a loss value of 19.7 billion rupiah according to a report from Munhwa Broadcasting Corporation (MBC). The research method used by the author is a statutory approach (the statue approach) using normative law or (legal research) by examining legislation in the form of primary, secondary, and tertiary legal materials collected by means of literature study.From the research conducted by the author on the assessment of two regulations, it can be concluded that both countries apply the same rules for the protection of Neighboring Rights in accordance with the agreements in the Bern and Rome Conventions. Broadcasters have neighboring rights that are guaranteed privileges so that violations of the law can be subject to civil and criminal sanctions. The principle of Fair Use or exclusion is also applied by both countries, but no details are provided because they adopt the principle of common law where jurisprudence or previous judicial decisions become the source of law.